Co-targeting of glial activation and inflammation by tsRNA-Gln-i-0095 for treating retinal ischemic pathologies - Ying Zhang; Yan Ma; Yu-Ke Ji; Yi-Fei Jiang; Duo Li; Wan Mu; Mu-Di Yao; Jin Yao; Biao Yan (Cell Communication and Signaling)
Abstract Ischemic retinopathies are the major causes of blindness, yet effective early-stage treatments remain limited due to an incomplete understanding of the underlying molecular mechanisms. Significant changes in gene expression often precede structural and functional alterations. Transfer RNA (tRNA)-derived small RNAs (tsRNAs) are emerging as novel gene regulators, involved in various biological processes and human diseases. In this study, tsRNA-Gln-i-0095 was identified as a novel regulator, which was significantly upregulated in retinal ischemia/reperfusion (I/R) injury. Reducing the levels of tsRNA-Gln-i-0095 suppressed reactive gliosis, lowered inflammatory cytokine levels, and protected retinal ganglion cells from I/R injury. These effects led to reduced structural and functional damage, inhibited glial activation and inflammation, and enhanced neuronal function. Mechanistically, tsRNA-Gln-i-0095 downregulated the expression of NFIA and TGFBR2 through a miRNA-like mechanism. Collectively, this study highlights the potential of targeting tsRNA-Gln-i-0095 as a novel therapeutic approach to reduce retinal I/R injury and preserve visual function. Graphical abstract